2021
DOI: 10.1080/10962247.2020.1853629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of OSPM against air quality measurements in Brazil – the case study of Fortaleza, Ceará

Abstract: The contribution of vehicle emissions to air pollution is considered a large environmental and health problem in big Brazilian cities caused, among others, by slow renewal of the old vehicle fleet. Brazilian studies usually only consider traffic-related issues in transportation analysis, with minor assessments of emissions and close to non-existent assessment of air quality. On this background, this research aimed to calibrate and evaluate the Operational Street Pollution Model (OSPM ® ) to Brazilian condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In recent times cities are undergoing severe transformations in which areas for sport and leisure are increasingly being suppressed, and so people are using areas with low environmental quality for physical activities, or even streets with high tra c (Rocha et al 2016;Marques et al, 2019;Dias et al, 2020;Bertoncini et al, 2021). According to Cajazeiras et al (2022), bacteria represented from 76% to 91% of the suspended microbiota in three outdoor areas used for physical activity, speci cally Genus Bacillus was the main representative of Gram positive and Enterobacter genus the most frequently identi ed among Gram-negative, while Aspergillus and Penicillium genera were the dominant among fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times cities are undergoing severe transformations in which areas for sport and leisure are increasingly being suppressed, and so people are using areas with low environmental quality for physical activities, or even streets with high tra c (Rocha et al 2016;Marques et al, 2019;Dias et al, 2020;Bertoncini et al, 2021). According to Cajazeiras et al (2022), bacteria represented from 76% to 91% of the suspended microbiota in three outdoor areas used for physical activity, speci cally Genus Bacillus was the main representative of Gram positive and Enterobacter genus the most frequently identi ed among Gram-negative, while Aspergillus and Penicillium genera were the dominant among fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the air pollution caused by automobile exhaust is more detrimental to human health (F abio et al, 2021;Pathak et al, 2021). Studies have shown that transportation has become the fastest growing sector of global energy consumption and greenhouse gas emissions, among which fuel vehicles are one of the significant reasons for the rise of carbon emissions and air pollution (Zhang et al, 2020;Dias et al, 2021;Makar et al, 2021). Very recently, new energy vehicles (NEVs) using clean energy can lessen carbon emissions to a certain extent, effectively decrease atmospheric pollution and promote sustainable energy consumption (Zheng et al, 2020;Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%